หนังสือเรื่อง "ความยุติธรรม" ผู้แปล สฤณี อาชวานันทกุล - พ่วงพร้อม, วรรณา (วารสาร ศึกษาศาสตร์ มมร, 2017)
บทวิจารณ์หนังสือเรื่อง ความยุติธรรม (Justice) นี้ เป็นผลงานเขียนของไมเคิล แซนเดล  ซึ่งเป็นอาจารย์สอนการเมืองในมหาวิทยาลัยฮาร์วาร์ด แปลโดยสฤณี อาชาวนันทกุล หนังสือได้กล่าวถึงหลักการในการตัดสินความยุติธรรมที่แยกออกตามหลักอรรถประโยชน์หลักประโยชน์นิยม สิทธิและหน้าที่ตามหลักการของอิมมานูเอล ค้านท์ และหลักอิสรนิยมหลักเสรีนิยม ของอริสโตเติล พบว่า รูปแบบการนำเสนอสามารถสะท้อนถึงความยุติธรรมส่วนหนึ่งเกิดประโยชน์ทางด้านการนำมาใช้ แต่เรื่องความคิดของบุคคลไม่สามารถนำมาตัดสินได้ เพราะลักษณะของการเมืองเป็นกระบวนการที่สามารถแปรเปลี่ยนไปตามสถานการณ์ของระบบ สำหรับเนื้อหามีความหลายหลาย และซับซ้อนอาจจะมีความยากสำหรับผู้ที่จะเข้ามาอ่านโดยไม่มีเป้าหมาย จึงมีความเหมาะสมกับกลุ่มนักกฎหมาย นักการเมือง และนักปรัชญา เพราะเนื้อหาเป็นเรื่องที่จะต้องใช้ความคิดที่สลับซับซ้อนต้องทำความเข้าใจ ผู้อ่านจึงต้องเป็นนักคิดอยู่ในตัวเมื่ออ่านแล้วจะได้นำข้อคิดที่ได้นำไปช่วยให้เกิดความยุติธรรมในสังคมต่อไปได้ Abstract The contents of the book Justice have used the principle to settle a fair split as follows: 1 by the main utility, utilitarianism. 2. The rights and obligations by Emmanuel Kant. 3 major liberal libertarian principles of Aristotle. The  story seeks to provide readers with a fair answer. The complex issues debated whether to get answers about what happened to the society. The  individuals are the reasons that led to universal moral principles. To Judge by the conscience, justice, freedom and the rule of law. Chapter 1 to Chapter 10, the final chapter is the main conscience on human rights at the long-term benefits. Political make a good habits and create good citizens. But if there is a debate on religious or worldly interests. It is inconsistent with freedom. Hence, justice should be impartial of vision. Racing for some people take a good bad guy, good way take a all good, scramble it take no one good, this is what people should be used to create a society with high moral principles intact.